Violência, mídia e velhice: o idoso nas páginas policiais de Pernambuco - Souza, Andrea Carolina Veras Oliveira Pereira de (2009)
The development of technologies has been one of the responsible factors, in the last decades, for the ageing of the population, which has a direct effect on the life of societies and of the individuals that compose them. It has been responsible, also, for the radical changes in the way information is generated, disseminated and absorbed. If, due to the growth of the elderly population, the person started to be treated as ugly, useless and unproductive , the growth of the means of communication made the news start to be treated as symbolic goods, a product with defined economic value. Understanding what the media shows, what it does not show, how the selection is made and with what consequences, especially when elderly individuals become news, led to the formulation of the question that guided the present investigation: how does the crime section of the newspapers from the city of Pernambuco (northeastern Brazil) cover violence and old age? Data were collected through the selection of texts concerning old age and violence, in newspapers from the archives of the Social Communication unit of the Civil Police of Pernambuco, in the years 2005 and 2006. These archives are related to prisons, police operations, death, people being run over, and violence in general. They are: Jornal do Commercio, Diário de Pernambuco and Folha de Pernambuco, daily newspapers that have a large circulation in the entire State. Every day, from Sunday to Saturday, these matters were cut out from the newspapers and filed, identifying the section and vehicle of communication that published news about people aged 60 or older, which is considered by the Senior Citizen Statute as the limit for the beginning of their protection. To organize the selected material, it was essential to develop a semi-structured questionnaire, with closed and open questions, whose answers were keyboarded in the software Statistical Package for the Social Sciences (SPSS), for the statistical treatment of the data. The study found 219 pieces of news involving elderly people and violence, in 2910 issues, in the period from January 2005 to December 2006. Of these, 169 clippings refer to the elderly as victims of violence and 50 to elderly individuals as being accused of violence. The study revealed that the media publishes the crimes in which the elderly are victims. It also showed that there is space for the publication of cases in which the elderly are the authors, not only victims. The proportion between victims and authors indicated a higher frequency of crimes committed against the elderly, but there was a significant incidence of crimes committed by the elderly. An interesting aspect of this scenario is the fact that the elderly are no longer presented almost exclusively as good , wise people and with no worries other than living their lives. The newspapers coverage concentrated on physical aggressions. The pattern of violence exposure obscures the visibility of the crimes that most affect the elderly in their daily lives, that is, domestic violence, apprehension of benefit cards and apprehension of the benefits themselves. Therefore, there is no allocation of public resources to face these crimes. Pieces of news on violence against the elderly are not sufficiently published